Response of groundnut (Arachis hypogaea L.) in sole crop and in intercrop with cassava (Manihot esculenta Crantz) to lime in an Ultisol in Bas Zaire - Osiname, O.; Muamba, T. (1995)
Field trials were carried out in M'Vuazi, Bas Zaire, to test the response of groundnuts (cv P43), planted sole or intercropped with cassava (cv Kinuani), to lime application. Groundnuts responded significantly to low rates of lime (250-500 kg ha-1). Maximum cost, benefit ratio of 1:7 was obtained when 500 kg lime ha-1was applied. Whether it was planted sole or intercropped with cassava, critical soil Ca level for groundnuts was estimated at 0.6 cmol kg-1. There was no cassava root yield response to the lime application at a soil Ca level of 0.11 cmol kg-1. Lime application below 2000 kg ha-1 did not significantly change the surface soil pH and did not affect the subsoil chemical properties. The main effects of lime on groundnuts were, therefore, to supply adequate Ca to: (1) produce maximum number of mature pods and (2) diminish the incidence of unfilled pods.